The relationship between hypovitaminosis D and foot and ankle pathologies: An integrative review (Research, Society and Development, 2024)
Objectives: To review the available literature on the relationship between hypovitaminosis D and foot and ankle pathologies, focusing on the musculoskeletal system and the prevalence of fractures, in order to investigate the harm caused by low levels of 25-hydroxyvitamin D to human health. Methods: This is an integrative review. Articles were selected from the PubMed platform, published until 2023, obtained by combining the descriptors “Vitamin D deficiency”, “Pathologies”, “Fractures”, “Foot” and “Ankle”, in response to the guiding question: “Hypovitaminosis D and foot and ankle pathologies, is there a relationship?". Results: 22 articles published between 2009 and 2023 were included and data related to them were extracted. The findings were categorized into manifestations in the osteoarticular, muscular and vascular systems. Osteoarticular manifestations were predominant. Lower bone consolidation rates, longer healing time and higher refracture rate were the main relationships presented. Muscular manifestations included reduced muscle strength related to the hypovitaminosis, although 1 of the studies found no relationship. The vascular findings are related to vitamin D insufficiency and peripheral arterial disease. Rickets and osteomalacia secondary to the phosphaturic mesenchymal tumor of soft tissues of the foot, a rare condition that leads to hypovitaminosis D, were also addressed. Conclusion: Hypovitaminosis D establishes a cause and consequence relationship with foot and ankle pathologies, with the osteoarticular, muscular and vascular systems being the most affecteds.